The Effectiveness Of Behavioral Concept With Modeling Techniques Through Lesson Study To Improve Self Nurturance Of Class X BDPM A Students State SMK Negeri 1 Singaraja - Ngurah Adi Mahendra; I Ketut Dharsana; Ni Ketut Suarni (Department of Guidance and Counseling, FIP, Undiksha, 2019)
The purpose of this study was to determine the effectiveness of Behavioral Counseling with a modeling technique through lesson study to improve Self Nurturance in class X BDPM A SMK Negeri 1 Singaraja. This research includes